HUBUNGAN ANTARA USIA DAN BEBAN KERJA DENGAN KELELAHAN KERJA OPERATOR PRODUKSI PERUSAHAAN LISTRIK: Related Age and Workload with Fatigue Work of Operator Production in Electrical Company - Ria Efridha Rahmayani; Erwin Dyah Nawawinetu (Lembaga Penelitian dan Terapan untuk Kesehatan Jiwa (Lenterakaji), 2018)
Fatigue is a condition that affect the efficiency, endurance, and safety of the work in general. The specific objective of this research was to study the internal factors (individual characteristics) and external factors (work system) associated with fatigue in the production operator in PT PJB UP Paiton. This research was a descriptive observation. The variables studied were factors age, years of service, nutritional status,workload based on the pulse, occupation, job variation, the state perseption of the lighting, noise exiting in the workplace according to the respondents. Fatigue was measured using a questionnaire measuring instrument feeling fatigue (KAUPK2). The result showed that the majority of respondents experienced fatigue of â€œmediumâ€ level (73,33%). Variables related to the level of fatigue of respondents were factors ages 43- 48 years (75%), work period 11-17 years (72.72%), nutritional status obesity 2 (58.71%), the heavy workload (81.81%), variety monotonous work (76.92%), state lighting (40%) and the state of the noise (76.92%). It is recommended to the company to provide leaflets and benner for the worker related to fatigue information and providing information how to choose a balanced diet according to the needs of energy. The management also have to suggest the operator to follow the exercises program once a week